Acute postictal cerebral imaging. - Silverstein, A M; Alexander, J A (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Imaging of postictal patients is performed to investigate causes of seizure, such as space-occupying lesions or other "structural" processes; however, abnormalities may be found that reflect physiological or pathologic alterations due to seizure activity. The purpose of this study was to determine the brain imaging findings in patients in the immediate postictal period who presented with altered mental status or weakness.METHODS Ten patients who were examined for postictal neurologic derangement were studied (nine by CT and one by MR imaging) within 12 hours of ictus. Four of the CT studies and the one MR study included administration of contrast material. Follow-up examinations were performed 1 day to 11 months later. These studies were reviewed retrospectively.RESULTS CT findings included focal gyral swelling (10/10), effacement of adjacent cortical sulci (2/10), decreased gyral attenuation by CT (8/9), and mild to moderate gyral enhancement after injection of contrast material (5/5). MR imaging findings included gyral swelling, increased signal intensity on T2-weighted images, and enhancement after injection of contrast agent. The abnormalities were located in the frontal lobes (9/10, with bilateral involvement in 6/10), the parietal lobes (4/10), the temporal lobes (2/10), and the occipital lobe (1/10). Follow-up studies revealed complete or subtotal reversal of these abnormalities.CONCLUSION Although there are numerous causes of gyral swelling and enhancement, such as infarction and neoplasm, if these conditions are reversible and correspond to clinical findings, then the differential diagnosis is narrowed to postictal change, reversible ischemia, complicated migraine, or resolved inflammation/infection.